Analysis of high streets of Istanbul: a proposal for strategic management approach. Issue 8 (3rd August 2022) - Tufekci, N. Gokce; Arslanli, Kerem Yavuz
ABSTRACT: This paper analyses the high streets of Istanbul within the context of high street management through four dimensions of location and movement, physical fabric, real estate & land use and exchange, and suggests a comprehensive approach to manage these commercial axes. While analysing the chosen study areas of Istiklal Street, Bagdat Street and Nisantasi District under the given topics, this paper makes use of analyses regarding transportation network, footfall, commercial and non-commercial use, prime rental values, besides a literature review to have an understanding towards the nature of each case study area. The results imply that despite their differences, all three study areas face certain issues that point out the lack of comprehensive strategic approaches to their management. Towards the high streets of Istanbul, this paper proposes a management approach embracing three main goals: (1) to constitute a brand image, (2) to decrease the vulnerability against macroeconomic factors and (3) to maintain vitality and viability of these axes. To overcome the complexities regarding management issues, this paper suggests an organizational and institutional approach, dedicated to considering the interests of all users on high streets.